2014
DOI: 10.1111/nmo.12443
|View full text |Cite
|
Sign up to set email alerts
|

Site and mechanism of morphine tolerance in the gastrointestinal tract

Abstract: Opioid-induced constipation is a major clinical problem. The effects of morphine, and other narcotics, on the gastrointestinal tract persist over long-term use thus limiting the clinical benefit of these excellent pain relievers. The effects of opioids in the gut, including morphine, are largely mediated by the μ-opioid receptors at the soma and nerve terminals of enteric neurons. Recent studies demonstrate that regional differences exist in both acute and chronic morphine along the gastrointestinal tract. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 48 publications
1
43
0
1
Order By: Relevance
“…[34][35][36] Recent in vitro studies in rodents has demonstrated tolerance to opioids in the upper, but not the lower GI tract. 37,38 Therefore differences in tolerance may partly explain our findings although direct translation to human in vivo physiology is highly questionable. 39 No associations between questionnaire scores and transit times were found.…”
Section: Discussionmentioning
confidence: 65%
“…[34][35][36] Recent in vitro studies in rodents has demonstrated tolerance to opioids in the upper, but not the lower GI tract. 37,38 Therefore differences in tolerance may partly explain our findings although direct translation to human in vivo physiology is highly questionable. 39 No associations between questionnaire scores and transit times were found.…”
Section: Discussionmentioning
confidence: 65%
“…However, previous animal studies suggest that while tolerance may develop to the analgesic effects and upper GI motility upon repeated morphine administration, tolerance does not develop in the colon. 35,36 To the authors knowledge no similar studies exist in humans, but if the preclinical results can be translated to humans, the outcomes of a clinical study would likely be either similar to ours or potentially more profound due to the longer treatment and/or higher doses. Nonetheless, in clinical studies, confounding factors that can affect gut function, such as concomitant drug use, immobility, dehydration, anxiety, depression, and anorexia are difficult to avoid and may bias results.…”
Section: 34mentioning
confidence: 67%
“…OIC can limit opioid therapy and may adversely impact patient adherence, adequate pain control, and patient function and in rare case even causes stercoral perforation, a potentially fatal complication 9,10. Treatment options for OIC have typically included a bowel regimen with lifestyle modifications and nonpharmacological strategies to be supplemented with conventional laxatives.…”
Section: Introductionmentioning
confidence: 99%